Giant snail : the end of the tale ? - Nobime, Victor (Technical Centre for Agricultural and Rural Cooperation, 1998)
Victor Nobime, from CREDAC in Benin, reports having received 'a flood of mail' after his message in Mailbox in Spore 71 : in one month, he received mail from more than 100 readers in twelve African countries about the giant African snail. He remarks...